Qurʾānic hermeneutics: al-Ṭabrisī and the craft of commentary - Fudge, Bruce (Routledge studies in the Qurʾān, 2011)
The genre of scriptural commentary in Islam -- al-Ṭabrisi: a twelfth-century exegete of Khurasan -- Language and knowledge in Majmaʻ al-bayan -- Commentary and Qurʼanic narrative -- Qurʼanic hermeneutics and the Muʻtazila